Inhibition of SERPINe1 reduces rhabdoviral infections in zebrafish. Issue 1 (November 2015) - Estepa, Amparo; Coll, Julio
Abstract: While exploring the molecular mechanisms behind the fin hemorrhages that follow zebrafish ( Danio rerio ) early infection with viral haemorrhagic septicemia virus (VHSV), we discovered that most serpin (ser inep roteasein hibitor) gene transcripts were upregulated, except those of serpine1 . Surprisingly, only SERPINe1 - derived 14-mer peptide and low molecular weight drugs targeting SERPINe1 (i.e. tannic acid, EGCG, tiplaxtinin) inhibited in vitro infections not only of VHSV, but also of other fish rhabdoviruses such as infectious hematopoietic necrosis virus (IHNV) and spring viremia carp virus (SVCV). While the mechanisms that inhibited rhabdoviral infections remain speculative, these and other results suggested that SERPINEe1-derived peptide specifically targeted viral infectivity rather than virions. Practical applications might be developed from these studies since preliminary evidences showed that tannic acid could be used to reduce VHSV-caused mortalities. These studies are an example of how the identification of host genes targeted by viral infections using microarrays might facilitate the identification of novel prevention drugs in aquaculture and illuminate viral infection mechanisms. Highlights: Zebrafish rhabdoviral-coagulation were studied by using microarrays. Fin haemorrhages correlated with upregulation of most serpin genes. However, serpine1 was not altered by rhabdoviral infections. Only serpine1- derived peptides neutralized rhabdoviruses in vitro . Serpine1 inhibitors reduced VHSV-mortalities in vivo .